Design and experiment of the ditching device for wheat seeders capable of ditching sloped drainage furrows in rice-wheat rotation areas - Wang, Quanyu; Peng, Ming; He, Jin; Lu, Caiyun; Wang, Chao; Tong, Zhenwei (International Journal of Agricultural and Biological Engineering, 2025)
To solve the problem of field waterlogging during wheat sowing in rice-wheat rotation areas, which causes sticky and wet soil, thus affecting the growth of wheat, this paper proposed a sloped ditching method based on laser alignment technology, and designed a combined ditching device with a front ditching shovel (FDS) and a rear ditching plow (RDP) to create sloped drainage furrows when sowing wheat. The key factors affecting the performance of RDP and value ranges were determined through theoretical analysis. Through discrete element method (DEM) simulation, the influence of different structural parameter combinations on slope stability was studied, and the optimal parameter combination was determined as the soil lifting angle of 50°, the minimum element angle of 35°, and the maximum element angle of 40°. The field test showed that the ditching device can effectively create sloped trapezoidal drainage furrows. The slope stability coefficient and slope accuracy coefficient were both greater than 85%, which meets the requirements of drainage. This paper provides a new ditching method and theoretical basis for the development of a sowing and ditching combined machine in rice stubble fields. Keywords: rice-wheat rotation, laser, wheat seeder, sloped drainage furrow, discrete element methodDOI: 10.25165/j.ijabe.20251801.8934Citation: Wang Q Y, Peng M, He J, Lu C Y, Wang C, Tong Z W. Design and experiment of the ditching device for wheat seeders capable of ditching sloped drainage furrows in rice-wheat rotation areas. Int J Agric & Biol Eng, 2025; 18(1): 154–164.